2010
DOI: 10.1016/j.visres.2009.08.024
|View full text |Cite
|
Sign up to set email alerts
|

Decoupling location specificity from perceptual learning of orientation discrimination

Abstract: Perceptual learning of orientation discrimination is reported to be precisely specific to the trained retinal location. This specificity is often taken as evidence for localizing the site of orientation learning to retinotopic cortical areas V1/V2. However, the extant physiological evidence for training improved orientation turning in V1/V2 neurons is controversial and weak. Here we demonstrate substantial transfer of orientation learning across retinal locations, either from the fovea to the periphery or amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
97
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 106 publications
(107 citation statements)
references
References 16 publications
10
97
0
Order By: Relevance
“…Zhang et al, 2010;Zhang and Yang, 2014;Xiong et al, 2016). Therefore, we suspected that similar techniques could also be effective for the current learning tasks.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang et al, 2010;Zhang and Yang, 2014;Xiong et al, 2016). Therefore, we suspected that similar techniques could also be effective for the current learning tasks.…”
Section: Resultsmentioning
confidence: 99%
“…Zhang et al, 2010;Zhang and Yang, 2014;Xiong et al, 2016) and that the learning effect can even transfer to the opposite visual field represented by the untrained brain hemisphere (Wang et al, 2012). For example, Vernier learning can transfer to a new location or orientation completely if the observers receive additional exposure of the new location or orientation via performing an irrelevant task (Wang et al, 2012(Wang et al, , 2014J.Y.…”
Section: Introductionmentioning
confidence: 99%
“…1-3) and retinal locations (Xiao et al, 2008;Zhang et al, 2010) challenges the existing models of perceptual learning. First, the complete learning transfer contradicts V1-based models (Adini et al, 2002;Teich and Qian, 2003;Zhaoping et al, 2003) as well as reweighting models that place the decision unit in the visual cortex at a post-V1 stage (Poggio et al, 1992;Dosher and Lu, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…We are also currently investigating how much exposure is needed for reactivation. In one study, we found that ϳ200 trials of pretest in the periphery enables complete transfer of foveal orientation learning to the periphery (Zhang et al, 2010), indicating that this process could be very fast for certain tasks. Without the pretest, there is no transfer (Schoups et al, 1995).…”
Section: Rule Application: Specificity and Transfermentioning
confidence: 99%
See 1 more Smart Citation